An intelligent approach to recyclability evaluation in automobile design - Taha, Z.; Sakundarini, N.; Raja Ghazilla, R.A.; Gonzalez, J. (2009)
An automobile comprises of thousands of parts of which 74-75% is composed of ferrous and nonferrous material and 8-/0% are from plastics, and typically only less than 75% of weight can be recycled and the rest cannot. As a result this leads to an increasing number of landfill required. Unfortunately, there is no more space available. With the importance of environmental protection and sustainable development; recyclability of materials is now becoming increasingly important in automobile design. Recyclability measures the efficiency of material recycling. Due to environmental regulation, automobile manufacturers are working to improve recyclability as well as reducing amount of recycle material to be used in new vehicles. One approach to evaluating recyclability during automobile design is mandatory needed to asses and give consideration whether the design has meet certain recyclability level. Although many approaches have been proposed by several authors, there is still a need for an intelligent solution that combines CAD system with recyclability evaluation in a single application. The purpose is to incorporate environmental consideration during the design phase. This paper attempts to propose an approach for recyclability evaluation using fuzzy method. A case study on an automobile s side mirror parts is presented to give clear figure how recyclability evaluation works.